2002
DOI: 10.1121/1.1494803
|View full text |Cite
|
Sign up to set email alerts
|

A multiple regression model for urban traffic noise in Hong Kong

Abstract: This article describes the roadside traffic noise surveys conducted in heavily built-up urban areas in Hong Kong. Noise measurements were carried out along 18 major roads in 1999. The measurement data included L10, L50, L90, Leq, Lmax, the number of light vehicles, the number of heavy vehicles, the total traffic flow, and the average speed of vehicles. Statistical analysis using the analysis of variance (ANOVA) and Tukey test (p<0.05) reveals that the total traffic flow and the number of heavy vehicles are the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 11 publications
2
26
0
1
Order By: Relevance
“…However, a study in Hong Kong showed that the increment of error when adopting the CRTN model might occur by more than 10 dB(A), especially when there were buildings on both sides of a road [21]. Another study in Hong Kong by [22] discovered an overestimation of 2 to 6 dB(A) produced by the CRTN model. On the other hand, [23][24] is the angle view in degrees?…”
Section: (Equation 11)mentioning
confidence: 99%
“…However, a study in Hong Kong showed that the increment of error when adopting the CRTN model might occur by more than 10 dB(A), especially when there were buildings on both sides of a road [21]. Another study in Hong Kong by [22] discovered an overestimation of 2 to 6 dB(A) produced by the CRTN model. On the other hand, [23][24] is the angle view in degrees?…”
Section: (Equation 11)mentioning
confidence: 99%
“…Avaliação do ruído de tráfego noturno -estudo de caso na cidade de Curitiba, Brasil et al, 2003). Estes estudos procuraram correlacionar parâmetros do tráfego rodoviário, como composição e volume de tráfego, com os níveis sonoros, utilizeo técnicas de regressão estatística (PRASCEVIC et al, 1997;CVETKOVIC et al, 1998;SATTLER, 1999;TO et al, 2002). Contudo, a maioria dos modelos são desenvolvidos para análise do ambiente noturno e tendo como base a regressão logarítimica, sem que seja considerada a multiplicidade do modelo (PAZ e ZANNIN, 2010).…”
Section: Introductionunclassified
“…16,17 To et al (2002) reported that road traffic noise levels in L 10,30-min measured at kerbsides ranged from 73.4 dBA to 91.4 dBA for roads with the total traffic flow between 540 and 4836 vehicles per hour. Although many people are exposed to high noise levels throughout the day 17 and like to attend social and cultural events including concerts for entertainment, they cannot tolerate additional noise exposure if the events take place close to where they live.…”
Section: Lessons Learnt From Hong Kong Open-air Music and Cultural Evmentioning
confidence: 99%
“…Hong Kong is a highly congested city and road traffic noise is one of the most serious environmental problems (To et al, 2002. 16,17 To et al (2002) reported that road traffic noise levels in L 10,30-min measured at kerbsides ranged from 73.4 dBA to 91.4 dBA for roads with the total traffic flow between 540 and 4836 vehicles per hour.…”
Section: Lessons Learnt From Hong Kong Open-air Music and Cultural Evmentioning
confidence: 99%